Sinks and Sources of Intracellular Nitrate in Gromiids - Høgslund, Signe; Cedhagen, Tomas; Bowser, Samuel S.; Risgaard-Petersen, Nils (Frontiers in Microbiology, 2017)
A substantial nitrate pool is stored within living cells in various benthic marine environments. The fate of this bioavailable nitrogen differs according to the organisms managing the intracellular nitrate (ICN). While some light has been shed on the nitrate carried by diatoms and foraminiferans, no study has so far followed the nitrate kept by gromiids. Gromiids are large protists and their ICN concentration can exceed 1000x the ambient nitrate concentration. In the present study we investigated gromiids from diverse habitats and showed that they contained nitrate at concentrations ranging from 1 to 370 mM. We used 15N tracer techniques to investigate the source of this ICN, and found that it originated both from active nitrate uptake from the environment and from intracellular production, most likely through bacterial nitrification. Microsensor measurements showed that part of the ICN was denitrified to N2 when gromiids were exposed to anoxia. Denitrification seemed to be mediated by endobiotic bacteria because antibiotics inhibited denitrification activity. The active uptake of nitrate suggests that ICN plays a role in gromiid physiology and is not merely a consequence of the gromiid hosting a diverse bacterial community. Measurements of aerobic respiration rates and modeling of oxygen consumption by individual gromiid cells suggested that gromiids may occasionally turn anoxic by their own respiration activity and thus need strategies for coping with this self-inflicted anoxia.